Differences in the Physiological Indicators of Seed Germination and Seedling Establishment of Durum Wheat (Triticum durum Desf.) Cultivars Subjected to Salinity Stress - Manel Hmissi; Mohamed Chaieb; Abdelmajid Krouma (Agronomy, 2023)
To investigate the effects of salinity stress on durum wheat cultivars at the critical stages of germination and seedling establishment under salinity stress, a study was conducted on eight durum wheat cultivars (Karim, Khiar, Inrat100, Maali, Monastir, Portodur, Razeg, and Salim) subjected to an increasing salinity concentration by using sodium chloride (NaC) (0, 2, 4, 6, and 10 g L−1). Germination and seedling physiological parameters were measured and thoroughly analyzed. Salinity stress significantly decreased germination capacity (GC), germination rate (GR), final germination capacity (FGC), germination index (GI), mean daily germination (MDG), and velocity coefficient (Vc), whereas mean germination time (MGT) and the stress index (SI) increased. Plantlet growth and initial vigor (IV) were also significantly hampered. Regarding all these traits, the cultivars’ differences were revealed: Karim and Salim were the least affected, whereas Razeg and Maali were the most affected, and the other cultivars occupied an intermediate position. Depending on cultivar, salinity stress decreased the germination capacity and delayed its initiation. At low salinity stress (2–4 g L−1 NaCl), the osmotic effect (OE) was the main cause of germination inhibition, whereas at high salinity stress (6–10 g L−1 NaCl), the toxic effect (TE) dominated and irreversibly inhibited the germination process. The initial vigor and the stress index that clearly discriminate among the studied cultivars are useful traits for screening tolerant genotypes. Otherwise, durum wheat showed a higher plasticity with salinity at the germination stage, allowing it to develop better tolerance at this stage, as compared to early stage plantlet growth.